OPTIMIZATION OF KRI ASSIGNMENTS IN PUSHIDROSAL TO SUPPORT THE INDONESIAN SEA MAP SURVEY - Supriyono Supriyono; Okol Sri Suharyo; Anton Nugroho (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT Scheduling is an assignment activity that deals with a number of constraints. A number of events can occur in a time period and place / location so that the objective function is as close as possible to be fulfilled. In the decision-making hierarchy, scheduling is the last step before the start of an operation. The scheduling of KRI assignments at Pushidrosal is an interesting topic to discuss and find solutions to using mathematical methods. The scheduling process for the KRI Pushidrosal assignment is carried out to produce an annual ship movement schedule. This process not only requires fast follow-up, but also requires systematic and thorough steps. Where assignment scheduling is a quite complex combinatorial problem. Meanwhile, the current assignment schedule is considered inadequate because the calculations are carried out in a conventional manner. The ship assignment scheduling process in this study uses Integer Programming modeling to obtain an alternative operation scheduling. Scheduling observed was 7 ships in carrying out N number of operations for 52 weeks (1 year). This research begins with determining the scheduling decision variables and the constraints faced. Hard constrain limitations include: ship maintenance schedule, time and duration of each survey operation, the class of ships assigned to carry out operations and the number of vessels executing each operation. Meanwhile, soft constrain is the length of the operating vessel in a row. The mathematical formulation of the Integer Programming model consists of three indicators, one decision variable, two measuring parameters and five constraint functions. Furthermore, the determination of the best alternative scheduling is done using Microsoft Excel's Solver computation program. Keywords: Assignment, Integer Programming, Solver.